Real‐Time In‐Situ Monitoring of a Tunable Pentapeptide Gel–Crystal Transition. Issue 44 (18th September 2019) - Guterman, Tom; Levin, Maayan; Kolusheva, Sofiya; Levy, Davide; Noor, Nadav; Roichman, Yael; Gazit, Ehud
Abstract: Supramolecular gels often become destabilized by the transition of the gelator into a more stable crystalline phase, but often the long timescale and sporadic localization of the crystalline phase preclude a persistent observation of this process. We present a pentapeptide gel–crystal phase transition amenable for continuous visualization and quantification by common microscopic methods, allowing the extraction of kinetics and visualization of the dynamics of the transition. Using optical microscopy and microrheology, we show that the transition is a sporadic event in which gel dissolution is associated with microcrystalline growth that follows a sigmoidal rate profile. The two phases are based on β‐sheets of similar yet distinct configuration. We also demonstrate that the transition kinetics and crystal morphology can be modulated by extrinsic factors, including temperature, solvent composition, and mechanical perturbation. This work introduces an accessible model system and methodology for studying phase transitions in supramolecular gels. Abstract : Unusual phase tester : An accessible pentapeptide system for studying gel–crystal phase transitions in supramolecular gels is introduced. The system allows to continuously measure the kinetics and visualize the dynamics of this common gel‐destabilizing phase‐transition process in situ using non‐destructive microscopy‐based methodology.